Biodiversity drives the choice; linguistic diversity fine-tunes the direction: Ethnofloral megadiversity in the Mexican ethnobotany - Andrea Martínez-Ballesté; Renata Sõukand; Carlos Martorell; Diana Flores- Camargo; Raivo Kalle; Julia Prakofjewa; Alejandro Casas (PLoS ONE, 2026)
People around the world have developed distinctive sets of useful plants, known as ethnofloras, which comprise a significant portion of Earth’s biodiversity. However, little is known about the factors that determine the composition of these collections and how different groups use plants. These differences may increase with geographic distance and linguistic separation due to barriers to communication and a lack of similarity in locally-available species. Using published ethnobotanical information, we analyzed the divergence in the composition of wild-species and the ways plants are used among 22 Mexican ethnic groups that use 2,855 species. We standardized plant use into ten categories and recorded them for each plant species and ethnic group. Each ethnic group uses a very large number of species (α-diversity), but few species are shared with other groups. Consequently, species turnover (β-diversity) between ethnic groups is very high. As expected, geographic distance fostered high differentiation in species composition of ethnofloras, probably reflecting differences in wild floras. Linguistic proximity promoted ethnoflora composition similarity, suggesting that communication plays a role in shaping the set of plants that are used. Geographic proximity also promotes similarity in how plants are used, though it is unclear whether language also plays a role. This suggests that language barriers are quite permeable. Social interactions and the use of Spanish as a lingua franca may favor the convergence of uses. This study provides a novel analysis of ethnofloras. It emphasizes the value of cultural and biological diversity and their importance in shaping ethnobotanical heritage.